Evaluation of body-self-perception of sedentary individuals aged over 30 who attended fitness center classes - Engin Gezer; Gulten Herguner; Mahmut Gulle; Mehmet Cetın (Türk Spor ve Egzersiz Dergisi)
With this study; it was aimed to obtain multi-dimensional evaluation of body-self perception levels of sedentary individuals aged over 30 who attended fitness center classes. The population of the study was consisted of fitness centers located inHatayProvince. The sample was composed of 80 sedentary individuals (38 men and 42 women) who attended the selected fitness centers with random sampling. All of the subjects were included in the study with voluntariness principle. Pre-test and post-test method was used in order to conduct a more illustrative study. In the study; a personal information form designed by the researcher and "The Multidimensional Body-Self Relations Questionnaire” which was designed by Winstead and Cash and Turkish adaptation and new form of which was made by Dogan and Dogan were administered to the subjects. Means, standard deviations of all the data were calculated. Comparisons of pre-test and post-test scores of the subjects were made with Paired Samples t – test. It was checked whether or not the results were significant at 0.05 level and 0.01 level. As a result; there was significant difference in terms of gender whereas no difference existed in terms of age, economic status and educational status. Again; when pre-test and post-test scores with regard to the subscales of “The Multidimensional Body-Self Relations Questionnaire” were compared no significant difference was found.